Donor site morbidity and quality of life after microvascular head and neck reconstruction with free fibula and deep-circumflex iliac artery flaps - Schardt, Christopher; Schmid, Angela Margarete; Bodem, Jens; Krisam, Johannes; Hoffmann, Jürgen; Mertens, Christian (Journal of cranio-maxillofacial surgery, 2017)
Purpose: Bone defects after resective tumor surgeries often require the use of microvascular reanastomized bone grafts for reconstruction. The decision as to which specific flap is most suitable for the particular patient is dependent on various factors. The aspects donor site morbidity and quality of life are rarely taken into account in this connection. The aim of this study was to analyze whether these factors, in the future, should influence the choice of donor site. Material and methods: In this study, the donor sites of 46 patients with respect to deep-circumflex iliac artery (DCIA) and fibula flaps were analyzed using subjective and objective parameters. The primary outcome was postoperative pain measured by VAS. Postoperative complication evaluations as well as 2 orthopedic scores were implemented (American Orthopedic Foot and Ankle Society (AOFAS) AnkleHindfoot Score and Harris Hip Score) and the patients' quality of life was assessed using the 36-Item Short Form (SF-36) questionnaire to quantify donor site impairment. Results: Postoperative pain was rated with a mean value of 42.4 mm (SD 34.8) for the DCIA group and 36.9 mm (SD 37.1) for the fibula group (p ¼ 0.617). After a mean period of 13.72 months, pain was rated with a mean value of 15.3 mm (SD 21.7) for DCIA and 13.3 mm (SD 22.6 mm) for the fibula (p ¼ 0.763). Persistent pain, however, was recorded only in 11.11% of DCIA patients and 5.26% of fibula patients. Furthermore pain intensity was higher in the DCIA group. A changed gait pattern was observed in 59.26% of DCIA patients and 21.05% of fibula patients. DCIA patients required walking aids for walking and stair climbing more often. Looking at the results of the 2 orthopedic scores, fibula patients showed slightly better results. Concerning quality of life, patients after reconstructive surgery with DCIA flaps showed slight better results than patients in the fibula group. Conclusions: Taking the results of this study into account, the outcome in terms of pain, morbidity and quality of life did not show a significant superiority of any donor site.